2020
DOI: 10.1177/1941738120919331
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Factors of Female Runners With and Without Stress Fracture Histories: A Pilot Study

Abstract: Background: Female runners are at increased risk of stress fractures (SFs) compared with men. Literature is lacking with regard to best practice for preventing and treating SFs in women. The purpose of the study was to compare physiological measures and running-related factors between women of various ages and running abilities with and without a history of running-related SFs. Hypothesis: Women with and without SF histories will differ with regard to medical and menstrual history, bone health, body compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…This is the first study to exclude such individuals, which may augment confidence in using menstrual disturbances as an indicator of LEA, showing that BSI rate is increased in female distance runners with OA. Many studies that did not account for hormonal contraceptive use and organic causes of menstrual disturbance found no association between menstrual function and BSI (Kelsey et al, 2007;Johnston et al, 2020;Logue et al, 2019;Duckham et al, 2015;Micklesfield et al, 2007). LEA influences menstrual function via suppression of the hypothalamic-pituitary-ovarian axis and is often characterised by profound hypoestrogenemia and perturbation of several other hormones involved in the regulation of bone (re)modeling (e.g., insulin-like growth factor 1 and leptin) (Elliott-Sale et al, 2018;Gordon, 2010).…”
Section: Low Energy Availability and Bone Stress Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first study to exclude such individuals, which may augment confidence in using menstrual disturbances as an indicator of LEA, showing that BSI rate is increased in female distance runners with OA. Many studies that did not account for hormonal contraceptive use and organic causes of menstrual disturbance found no association between menstrual function and BSI (Kelsey et al, 2007;Johnston et al, 2020;Logue et al, 2019;Duckham et al, 2015;Micklesfield et al, 2007). LEA influences menstrual function via suppression of the hypothalamic-pituitary-ovarian axis and is often characterised by profound hypoestrogenemia and perturbation of several other hormones involved in the regulation of bone (re)modeling (e.g., insulin-like growth factor 1 and leptin) (Elliott-Sale et al, 2018;Gordon, 2010).…”
Section: Low Energy Availability and Bone Stress Injurymentioning
confidence: 99%
“…LEA and oestrogen deficiency are independently, and in combination, linked with impairments in bone strength (Hutson et al, 2021;Southmayd et al, 2017;De Souza & Williams, 2005). Several studies have shown that amenorrhoea or oligomenorrhoea (typically reported as fewer than nine menses over 1 year) are associated with increased BSI occurrence (Duckham et al, 2012;Ackerman et al, 2015;Bennell et al, 1999;Tenforde et al, 2013), whilst others have found no such association (Kelsey et al, 2007;Johnston et al, 2020;Logue et al, 2019;Micklesfield et al, 2007). Reasons for disparity are unclear; however, none of these studies accounted for hormonal contraceptive users and those with organic menstrual pathologies (such as polycystic ovarian syndrome).…”
Section: Introductionmentioning
confidence: 99%
“…Bone metabolic response to exercise comprises the processes of resorption, reversal, formation, and mineralization and bone metabolism markers are used to assess these processes [5]. Moreover, they have been used to assess stress fractures in athletes [6]. Thus, several sports medicine professionals use BMD and BMC, as well as bone turnover markers, to assess the bone health of athletes.…”
Section: Bone Metabolism Bone Mineral Content and Density In Elite Late Teen Female Sprintersmentioning
confidence: 99%
“…Currently, whole body dual-energy x-ray absorptiometry (DXA) measurements are used as a method to assess an individual's risk of stress fracture injury [5]. lower bone mineral density (BMD), bone mineral content (BMC) and reduced bone structural properties have been associated with stress fracture risk in some athletic population (cricketers (lumbar spine BMD, [6]), runners (tibial strength, [7]; hip BMD, [8]), triathletes (tibial cortex; [9]) and female athletes (trabecular BMD; [10]), but not in others (endurance athletes (triathletes and runners-whole body, lumbar spine and hip) [11] and runners (whole body, lumbar spine, hip, radius) [12][13]. The contrasting findings may be accounted for by the sport participated in, the likely difference in the pathophysiology of injury caused by the differing activity status of the participants (amateur and elite populations) in the aforementioned studies and the difference in the anatomical scan site.…”
Section: Introductionmentioning
confidence: 99%